1996
DOI: 10.1046/j.1365-2621.1996.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heat‐induced changes in Spanish commercial milk: hydroxymethylfurfural and available lysine content

Abstract: Hydroxymethyfurfural (HMF) content and loss of available lysine were measured as indices of heat damage in various Spanish commercial milks (pasteurized, UHT sterilized and in‐bottle sterilized milks) with similar processing dates. HMF level was determined by the traditional colorimetric procedure and by the reversed‐phase HPLC method. Available lysine was measured by an alternative method with o‐phthaldialdehyde as fluorescent marker. A significative relationship has been found between the HMF content and los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 22 publications
1
28
2
1
Order By: Relevance
“…This was, moreover, evidenced by the results obtained for the total lysine determined after complete acid hydrolysis, where only 5e13% lysine residues losses were observed at pH 5.8 and 8, respectively (Table 2). This was obviously due to the conversion of the chloramines of the lysine 3-amino group to the native lysine during the strong acid digestions applied (Nightingale et al, 2000). Although expected that the monochloramines of the 3-amino groups of the lysine residues would decarboxilate and loose ammonia leading to carbonyls formation, we observed that they led to only limited amounts of carbonyls, which is also in line with previous reports (Domigan, Charlton, Duncan, Winterbourn, & Kettle, 1995).…”
Section: Amino Acid Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was, moreover, evidenced by the results obtained for the total lysine determined after complete acid hydrolysis, where only 5e13% lysine residues losses were observed at pH 5.8 and 8, respectively (Table 2). This was obviously due to the conversion of the chloramines of the lysine 3-amino group to the native lysine during the strong acid digestions applied (Nightingale et al, 2000). Although expected that the monochloramines of the 3-amino groups of the lysine residues would decarboxilate and loose ammonia leading to carbonyls formation, we observed that they led to only limited amounts of carbonyls, which is also in line with previous reports (Domigan, Charlton, Duncan, Winterbourn, & Kettle, 1995).…”
Section: Amino Acid Compositionsupporting
confidence: 92%
“…The loss of reactive lysine was monitored using derivatization with ortho-phthaldialdehyde (OPA) in the presence of 2-mercaptoethanol (2-ME) which yields a fluorescent product with a maximum excitation wavelength of 340 nm and emission of 450 nm (Ferrer et al, 2003) and b-casein was used to prepare a calibration curve (Morales, Romero, & Jimenez Perez, 1996).…”
Section: Loss Of Reactive Lysinementioning
confidence: 99%
“…In the same line, a 10-15% greater blockage of lysine in sterilized versus UHT milk is mentioned by Finot et al [36] and Anantharaman and Finot [2]. Morales et al [37] report a loss of L 2% in UHT milk and L 6% in in-bottle sterilized milk. The fact that sterilization modifies whey proteins to a greater extent than the UHT processes could explain the above-mentioned differences [38,39].…”
Section: Effect Of Thermal Treatmentmentioning
confidence: 61%
“…In our system, HMF was not detectable in raw IF, but its concentration rapidly increased with temperature starting from 87°C. The IF model heated for 9.5 min contained 2.54, and 7.35 lM HMF at 110°C, the latter being in the range of concentrations described for UHT milk (Morales, Romero, & Jimenez-Perez, 1996. Surprisingly however, HMF levels reported in commercial IF were much lower, 0.60-1.29 lM (Albala-Hurtado, Veciana-Nogues, Marine-Font, & Vidal-Carou, 1998;Chávez-Servín, Castellote, & López-Sabater, 2006), although a higher HMF concentration would be expected than in UHT milk, because of the higher lactose content in IF than in cow's milk.…”
Section: Resultsmentioning
confidence: 99%